2021
DOI: 10.48084/etasr.4314
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hybrid Fibers on Punching Shear Strength of Concrete Flat Plates Exposed to Fire

Abstract: This study presents an investigation about the effect of fire flame on the punching shear strength of hybrid fiber reinforced concrete flat plates. The main considered parameters are the fiber type (steel or glass) and the burning steady-state temperatures (500 and 600°C). A total of 9 half-scale flat plate specimens of dimensions 1500mm×1500mm×100mm and 1.5% fiber volume fraction were cast and divided into 3 groups. Each group consisted of 3 specimens that were identical to those in the other groups. The spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The practice of using recycled waste for construction has gained worldwide popularity, as it can be deployed to manage waste sustainably and protect the environment balance by employing a variety of raw resources [8]. In [9], it was demonstrated that utilizing several fiber types can enhance the performance of concrete and produce superior results [9]. In [10], affordable materials were implemented to evaluate RPC castings.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of using recycled waste for construction has gained worldwide popularity, as it can be deployed to manage waste sustainably and protect the environment balance by employing a variety of raw resources [8]. In [9], it was demonstrated that utilizing several fiber types can enhance the performance of concrete and produce superior results [9]. In [10], affordable materials were implemented to evaluate RPC castings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current research is mainly concentrated on computational methods. Authors in [2,3] carried out experimental tests in order to understand the punching shear behavior of concrete slabs reinforced by steel collars and hybrid fibers. Author in [4] studied the limit state of local instability of steel column structures under axial compression using the energy method combined with the finite element method using fiber beam-column elements.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [10] outlined a simple theoretical method based on the yield line theory to predict the flexural capacity of a strengthened RC flat slab with unequal-leg steel angle plates. Adding fibers to the concrete made the flat plate fail in a more ductile mode, while the failure was sudden with brittle mode in slabs that contained no fibers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%